1970
DOI: 10.1099/00221287-62-3-341
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Resistance to Tetracycline in Staphylococcus aureus

Abstract: S U M M A R YWhen staphylococci, resistant to 4 pg. tetracycline/ml., were grown in nutrient media at subinhibitory levels of the drug, phenotypical resistance increased until the cocci grew with 160 pg. tetracyclinelml. Resistance increased most rapidly at the highest concentration of tetracycline which did not significantly inhibit growth. Increase in resistance was also obtained by pre-incubation with p-apo-5-oxy-tetracycline. Increase in resistance could be prevented by chloramphenicol and actinomycin D, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

1971
1971
1977
1977

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 9 publications
(5 reference statements)
1
31
0
Order By: Relevance
“…The macro-inducible tetracycline-resistant staphylococci described here appear to be typical of strains possessing wild-type plasmids (34), but neither macro-constitutive types, in which the genes specifying resistance are chromosomal, nor micro-constitutive strains, in which resistance is plasmid mediated, have previously been described.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The macro-inducible tetracycline-resistant staphylococci described here appear to be typical of strains possessing wild-type plasmids (34), but neither macro-constitutive types, in which the genes specifying resistance are chromosomal, nor micro-constitutive strains, in which resistance is plasmid mediated, have previously been described.…”
Section: Discussionmentioning
confidence: 69%
“…on the syntheses of ribonucleic acid and protein, this drug may be used to distinguish between selection of resistant organisms and induction of resistance involving repressor-operator structural gene interactions (34). Overnight cultures were diluted into fresh warmed broth and grown with aeration to culture densities of 2 x 108 organisms per ml.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the bacteriostatic antibiotics, tetracycline (TC), is a specific inhibitor of protein synthesis in vivo as well as in vitro (1,12,13). Studies carried out in several laboratories have shown that, unlike other types of bacterial resistance, TC resistance is not due to either the modification of ribosome(s) and of protein synthetic machinery or of enzymatic destruction of the drug (3,8,10).…”
Section: Discussionmentioning
confidence: 99%
“…In strains with inducible TC resistance, the mechanism of the resistance has been considered to be a specific decrease of permeability of the bacterial membrane (2,4,7,13). Recent studies by curing experiments and transduction to a rec-recipient revealed that almost all genetic determinants governing TC resistance in staphylococci are located on a plasmid (S. Mitsuhashi and M. Inoue, U.S.-Japan Scientific Seminar on Bacterial Plasmid, Hawaii, June 1972).…”
mentioning
confidence: 99%